Head CT Scan Procedure in Post-Traffic Accident Head Trauma Cases: A Case Study at Siloam Sriwijaya Hospital, Palembang - M.Hasbiansyah Putra Wibisono (JURNAL LENTERA ILMIAH KESEHATAN, 2026)
Head trauma resulting from traffic accidents is an emergency condition that requires rapid imaging to exclude life-threatening intracranial injuries. This study aims to describe the procedure and findings of non-contrast head computed tomography (NCCT) in a post-traffic accident head trauma case at the Radiology Department of Siloam Sriwijaya Hospital, Palembang. A descriptive case study design was applied. Data were obtained from NCCT images and validated radiology reports of a 25-year-old male patient examined on May, 2025, complemented by structured interviews with radiographers regarding technical protocols and workflows. The examination was performed using 120 kV, 350 mAs, 5-mm slice thickness for axial acquisition with 1–2 mm multiplanar reconstruction, a field of view of approximately 250 mm, a 512 × 512 matrix, and brain (WL/WW ≈ 40/80 HU) and bone window (WL/WW ≈ 400/2000 HU) settings. NCCT findings demonstrated no intracranial hemorrhage, midline shift, or mass effect. The main pathological findings were nasal bone fracture, septal deviation, and hemosinus involving the bilateral ethmoid sinuses and the left maxillary sine. The applied protocol was consistent with emergency radiology practice and adhered to the ALARA principle through appropriate parameter optimization and multiplanar reconstruction. These findings highlights the role of NCCT US a reliable first-line modality for rapid exclusion of critical intracranial injury while accurately detecting facial bone trauma in traffic accident-related head injuries.